Precise control of diazirine reduction to tune the mechanical properties of electrocuring adhesives - Ambrosi, Adriano (2022)
There is a growing interest in developing innovative adhesive materials that offer stimuli-responsive mechanical properties. Electrocuring adhesives exploit electric-field stimuli towards initiating and propagating polymerization reactions with projected benefits of on-demand adhesion and microelectronic control. Voltaglue is a recently developed biocompatible, water-based bioadhesive that combines a biomacromolecule (polyamidoamine, PAMAM) with a grafted electrochemical crosslinker (diazirine) where the former mediates viscoelastic properties and the latter voltage-based activation. Through this relatively simple design, a range of viscoelastic and adhesive properties are possible by controlling the intensity (voltage) and duration (coulombs) of the electric field. For the first time, bioadhesive properties are correlated to the moles of diazirine reduced during electrocuring via chronoamperograms. The method is based on the precise measurement of the charge exchanged during the reductive reaction which ultimately results in a series of voltage/time combinations that can be used to drive diazirine activation and charge quantitation. A strong correlation is finally observed between diazirine electrolysis and specific mechanical properties of the cured adhesive. This ultimately enables fine-tune control over the adhesive properties with benefits in a wide variety of applications ranging from electromagnetic biomaterials to additive manufacturing.